Identification of essential steps in laser procedure for twin–twin transfusion syndrome using the Delphi methodology: SILICONE study. (5th March 2015) - Peeters, S. H. P.; Akkermans, J.; Westra, M.; Lopriore, E.; Middeldorp, J. M.; Klumper, F. J.; Lewi, L.; Devlieger, R.; Deprest, J.; Kontopoulos, E. V.; Quintero, R.; Chmait, R. H.; et al.
ABSTRACT Objective To determine, by expert consensus, the essential substeps of fetoscopic laser surgery (FLS) for twin–twin transfusion syndrome (TTTS) that could be used to create an authority‐based curriculum for training in this procedure among fetal medicine specialists. Methods A Delphi survey was conducted among an international panel of experts (n = 98) in FLS. Experts rated the substeps of FLS on a five‐point Likert‐type scale to indicate whether they considered them to be essential, and were able to comment on each substep, using a dedicated online platform accessed by the invited tertiary care facilities that specialize in fetal therapy. Responses were returned to the panel until consensus was reached (Cronbach's α ≥ 0.80). All substeps that were rated ≥ 4 by 80% of the experts were included in the evaluation instrument. Results After the first iteration of the Delphi procedure, a response rate of 74% (73/98) was reached, and in the second and third iterations response rates of 90% (66/73) and 81% (59/73) were reached, respectively. Among a total of 81 substeps rated in the first round, 21 substeps had to be re‐rated in the second round. Finally, from the initial list of substeps, 55 were agreed by experts to be essential. In the third round, the 18 categorized substeps were ranked in order of importance, with 'coagulation of all anastomoses that cross the equator' and 'determination of fetoscope insertion site' as the most important. Conclusions A total of 55 substeps of FLS for TTTS were defined by a panel of experts to be essential in the procedure. This list is the first authority‐based evidence to be used in the development of a final training model for future fetal surgeons. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.